POTENTIAL CLINICAL SIGNIFICANCE OF UREASE ENZYME - Banerjee Sujoy; Aggarwal Aparna (European Scientific Journal, ESJ, 2013)
Urease belongs to the super family of amidohydrolases and phosphotriestreases. Urease involves the nitrogen metabolism; urea degradation; generating CO2 and NH3 from urea. Urease has wide clinical applications. Urease enzyme serves as a virulence factor and is responsible for pathogenesis in humans. Urease activity of microbial sources has contributed to the development of many diseases and urease from plant sources is used as vaccine against microbial infection on the basis of its inhibitory activity.